Hubungan Pemberian ASI Eksklusif dengan Kejadian Stunting pada Balita - Pradnyawati, I Gusti Ayu Mirah; Sipahutar, Ida Erni; Sulisnadewi, Ni Luh Kompyang (Jurnal Gema Keperawatan, 2023)
Stunting is a condition of toddlers who experience growth failure due to chronic malnutrition, toddlers become short for their age. One of the risk factors for stunting is the lack of nutritional intake of toddlers, including exclusive breastfeeding. Exclusive breastfeeding can help prevent stunting. The purpose of the study was to determine the relationship between exclusive breastfeeding and the incidence of stunting in toddlers in Tista Village, the working area of the Abang I Karangasem Health Center in 2023. The type of research used in this study was non-experimental with a correlational research design and cross sectionalapproach using non-probability sampling with purposive sampling technique. The sample size was 128 respondents. Data collection using exclusive breastfeeding questionnaires and anthropometry. The results showed that most mothers who had toddlers in Tista Village had exclusive breastfeeding as much as 85.2%. Most of the toddlers in Tista Village were with normal nutritional status 71.9%, followed by short nutritional status 19.5%, and very short nutritional status 8.6%. Hypothesis testing using the contingency coefficient test with a value of p=0.000 (?=0.05) and a value of r=0.439, it was concluded that there was a relationship between exclusive breastfeeding and the incidence of stunting in toddlers in Tista Village, the working area of the Abang I Karangasem Health Center in 2023. It is expected that mothers need to get health education about stunting, the importance of exclusive breastfeeding, and other factors that are at risk of stunting.